Niepożądani czerwonoarmiści, ignorowani niemieccy antyfaszyści i honorowani esesmani : o statusie prawnym i realiach grobów oraz cmentarzy wojennych radzieckich i niemieckich w Polsce - Mazurkiewicz, Jacek (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The first part of the article deals with the protection of personal rights in the statutory law of Poland: legal act of graves and war cemeteries and in four international agreements concluded by Poland with Russia, Ukraine, Belarus and Germany with regard to war cemeteries. In the second part of the essay the author writes about devastation and desecration of cemeteries of Soviet soldiers, the fate of the forgotten graves and German anti-fascist characters and honors given by representatives of Polish institutions, the army and the clergy in the burial places of the SS men
Keywords: graves and war cemeteries; soldiers of the Red Army; German anti-fascists; SS men